The stability of spherical clusters with respect to perturbations of finite amplitude - V. A. Antonov (Вісник Астрономічної школи, 2003)
The stability of gravitating systems – gaseous spheres and collisionless stellar systems – with respect to perturbations of arbitrary amplitude is considered.